The Resolute Women Characters, “Indramaya” and “Chitranggada” - Thapa, Rena (Journal of Fine Arts Campus, 2022)
This paper made study of two strong women characters Indramaya and Chitranggada in Bisheshwor Prasad Koirala’s Tin Ghumti (2004) and Sharada Sharma’a Kampa (2016) respectively. Drawing on feminist theory and gender theory, I analyzed these characters as real humans who are not immune of shortcomings, hardships and conundrums they face in their life. My effort was engrossed to explore how women’s sense of self esteem, freedom and existence is revered in these two novels. By resisting the imposed androcentric values these two characters choose to live their life independently saving their soul and individuality. Such characters can be found in Nepali society where they drift, fight, and claim their right to existence. The narrative, dialogues, and plot portrays these two women of the 21st century heroine, imperfect and sometimes absurd. True love is on the cards, but prohibited relationship nearly sinks them. But they realize and rise without remorse. They represent the world which is non-compliance with the world patriarchy has organized liberating oneself from the sense of inadequacies. They are the voice in the novel that is heard the loudest.